A lot of people are pointing you to stirlings formula to prove this. Although that is a perfectly acceptable route, you don't have to use if if you don't know it, and in fact you can show it in another way.
First off, stack overflow is horrible for math markup so what I'm going to write below is going to look ugly (nudge. nudge. devs of stackoverflow should follow math overflow's example and give some nice latex markup.)
That said, lets get on with things. The upper-bound log(n!) <= n log n is trivial.
The lower bound is not so trivial. I hope by now in your career you are familiar with Taylor series, if you aren't then you should quickly familiarize yourself with them because they are going to be one of your most potent tools for approximating things, or in this case bounds.
Note that
log(n!) = sum[i,1,n] (log i)
= sum[i,1,n] ( log ( (i/n) * n ) )
= sum[i,1,n] ( log ( (i/n) ) + log n ) )
= sum[i,1,n] ( log ( i/n ) ) + sum[i,1,n] ( log n )
= sum[i,0,n-1] ( log ( 1 - i/n ) + sum[i,1,n] ( log n )
now from taylor series
log( 1 - x ) = - sum[n,1, infinity] x^n/n for -1 < x < 1
so
log( 1 - i/n ) = - sum[k,1, infinity] (i/n)^k/k
= - (i/n)( 1 + (i/n)/2 + (i/n)^2/3 + ... )
>= - ( 1 + (i/n)/2 + (i/n)^2/3 + ... ) since (i/n) < 1
>= - ( 1 + (i/n) + (i/n)^2 + ... )
= - 1/(1-i/n) = n/(i-n)
so
log(n!) = sum[i,0,n-1] ( log ( 1 - i/n ) ) + sum[i,1,n] ( log n )
= sum[i,0,n-1] ( log ( 1 - i/n ) ) + n log n
>= sum[i,0,n-1] ( n/(i-n) ) + n log n
= n sum[i,0,n-1] ( 1/(i-n) ) + n log n
= - n sum[i,1,n] ( 1/i ) + n log n
= n ( log n - sum[i,1,n] ( 1/i ) )
let H_n = sum[i,1,n] ( 1/i ), then there exists a positive 0 < c < 1 such that H_n <= c log n
to see this note that
log(x) is bounded below by some a > 0 for all x > 2
and so the integral must be strictly greater than the sum (this is a general result for strictly positive functions that are bounded below by some a) :
H_n = sum[i,1,n] ( 1/i ) < integral[x,1,n] ( 1/x ) = log n for n >= 2
thus there must exist a constant such that H_n <= c log n with 0 < c < 1.
Then we have that
log(n!) >= n ( log n - H_n )
>= n ( log n - c log n )
= ( 1 - c ) n log n
proving the result.